Influence of sintering temperature on morphology and electrochemical performance of LSCF/GDC composite films as efficient cathode for SOFC. (20th August 2017) - Çelikbilek, Ӧzden; Siebert, Elisabeth; Jauffrès, David; Martin, Christophe L.; Djurado, Elisabeth
Abstract: Functional composite cathode films of 56:44 wt. % La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF)/Ce0.9 Gd0.1 O2-δ (GDC) films with two different microstructures denoted as coral and columnar were coated on a dense GDC electrolyte by electrostatic spray deposition (ESD) technique. The sintering temperature ( Ts ) was varied on the ESD films from 800 to 1100 °C in air to investigate the influence of sintering conditions on the microstructure, crystalline phases and electrode performances. The amount of porosity, grain growth and electrochemical performance were monitored for both microstructures by combining scanning electron microscope, x-ray diffraction and electrochemical impedance spectroscopies. The microstructures showed marked differences at the micro and nano-scales. The films with lower deposition temperature (columnar film, 300 °C) were observed to have accelerated and uncontrolled grain growth and inhomogeneous size distribution at elevated Ts than films with higher deposition temperature (coral film, 350 °C). Regardless of the microstructure, as low as 0.05 ± 0.01 Ω cm 2 at 650 °C were measured for the films sintered at low Ts (800-900 °C). The differences in resistance and activation energy values were evidenced at high Ts (≥ 1000 °C). The electrochemical processes are discussed in terms of resistance, capacitance and frequency distribution. This study reveals that ESD processing parameters play a critical role in sintering behavior and electrode performances of composite cathode films, mainly at high Ts (≥ 1000 °C).